Vitamin D receptor polymorphism and colorectal cancer-specific and all-cause mortality - Perna, Laura; Hoffmeister, Michael; Schöttker, Ben; Arndt, Volker; Haug, Ulrike; Holleczek, Bernd; Burwinkel, Barbara; Ordóñez Mena, José M.; Brenner, Hermann (Cancer epidemiology, 2013)
Background - The vitamin D receptor (VDR) gene is present in colorectal cancer (CRC) cells and its genetic variants have been associated with an increased risk of CRC. The association with colorectal cancer prognosis remains widely unexplored. - Methods - 1397 colorectal cancer patients participating in two cancer cohorts (ESTHER II and VERDI) and in a population-based case-control study (DACHS) were followed for 5 years. Unadjusted and adjusted hazard ratios for all-cause mortality (469 events) and CRC-specific mortality (336 events) were estimated for VDR variants rs731236 (TaqI), rs2228570 (FokI), rs11568820 (Cdx2), and rs1989969 (VDR-5132). - Results - No association was found between VDR polymorphism and CRC specific and all-cause mortality. Adjusted hazard ratios ranged from 0.79 (95% CI 0.57-1.12) to 1.14 (95% CI 0.89-1.46) for CRC-specific mortality and from 0.89 (95% CI 0.67-1.18) to 1.22 (95% CI 0.99-1.50) for all-cause mortality. All 95% confidence intervals included the null value. - Conclusions - Our findings do not support the hypothesis that the common VDR gene variants investigated in this study are of clinical relevance with respect to CRC prognosis.